Kiss - Mansell, Jill (Sourcebooks Landmark, 2019)
"When aspiring musician Izzy is knocked off her motorbike, she doesn't just lose her dignity--she loses both long-term boyfriends, her job, and her beautiful apartment. Gina, who caused the accident, has more important things to worry about: Her husband's mistress is pregnant and she's suddenly on her own. Why should she care about Izzy? Yet somehow, Gina finds herself opening her home to Izzy and her spirited teenage daughter. And it's there that Izzy meets heart-stoppingly handsome Sam, whose lingering kiss is all it takes for her to find the true love that has always eluded her--though there are just a few obstacles between that first kiss and her happily ever after..."--